Trend of genetics learning media research: A bibliometric analysis (1968-2024) - Isnaeni, Bekti; Kuswandi, Paramita Cahyaningrum; Paidi, Paidi; Mualimin, Mualimin (Universitas Wiralodra, 2025)
The use of learning media difficulty in comprehending complex material, the inability to effectively visualize microscopic objects that require specialized teaching aids or interactive media. This descriptive qualitative research, employing a bibliometric approach, aims to analyze research trends on learning media in genetics from 1964 to 2024. The analysis focuses on the volume and distribution of publications, the contributing countries, and the institutional affiliations, as well as key journals in the field. The research subject is learning media in genetics courses. Data collected through the Scopus website, using the keywords “genetic,” “learning,” and “media,” yielded 1,135 results, which were analyzed using R and Biblioshiny software. The trend in research on genetics learning media has increased year by year, with a sharp increase from 2017 to 2023. This result indicating that the research trend reached its peak in that year. The USA and China are the countries that contribute the most to publishing articles, suggesting potential for collaboration with various countries. The most active affiliation, with a total of 72 articles, is the University of California. The journal that contributes the most to genetics learning media is the Journal of Behavior Genetics. This research can serve as a reference for future researchers interested in studying genetics learning media, with the recommendation to combine multiple applications, such as Biblioshiny with Vosviewer, to ensure more precise and more valid findings. Additionally, using more specific keywords, such as e-modules, virtual reality (VR), augmented reality (AR), or game-based learning, is advised.